An ICT-based solid waste management system for smart cities: a case of municipality in India. (19th November 2021) - Jhaveri, Rutvij H.; Shah, Prerak S.; Patel, Neel N.; Patel, Dhrumil M.; Thanki, Shashank; Bhoi, Akash Kumar; Bhatia, Jitendra
Smart cities are technology enabled and data driven intelligent cities with prominent use of information and communication technology (ICT)-based technologies integrated with sensor devices. This paper proposes a low-cost, dynamic, energy-efficient and easily deployable smart solid waste management system for municipalities in urban localities. A kit comprising of a micro-controller, a pair of ultrasonic sensors and global system for mobile communication (GSM) module is installed into the garbage container. The contribution of this study can be seen in two folds. Firstly, the proposed system helps in achieving sustainable development goals namely, clean water and sanitation industry (SDG 6), innovation and infrastructure (SDG 9), sustainable cities and communities (SDG 11) and life on land (SDG 15). Secondly, contribution is the innovative solution for municipality solid waste management which could help in achieving three pillars of sustainability: economic, social and environmental, for sustainable development of future smart cities.